Polycyclic aromatic hydrocarbons in the work atmosphere. I. Determination in an aluminum reduction plant. - Bjørseth, Alf; Bjorseth, Olav; Fjeldstad, Per E (Scandinavian Journal of Work, Environment & Health, 1978)
The content of polycyclic aromatic hydrocarbons (PAH) in a Soderberg prebaked aluminum reduction plant and an anode plant was studied. Both stationary and personal sampling were used, and the samples were analyzed by glass capillary gas chromatography. In many samples more than 30 PAH and heterocyclic compounds were identified. Comparison of the results from the different plants revealed that the atmospheric PAH content was significantly higher in the Soderberg plant than in the others. However, the relative distribution of PAH components (PAH profile) was relatively constant in the prebaked and the anode baking plant, and different in the Soderberg plant. As a consequence of the variation in the pollution level among the different job categories, personal sampling showed a broader range of PAH concentrations than the stationary method.
Keywords: aluminum reduction plant; analysis; benzo(a)pyrene; determination; PAH; polycyclic aromatic hydrocarbon; sampling; work athmosphere